Synthesis, structural characterization, in vitro biological evaluation and in silico molecular docking of some new 1,2,3-Benzotriazole-based Schiff base derivatives - Shawkat Hayat; Mohamed S. Othman; Hayat Ullah; Amina Qureshi; Fazal Rahim; Sadiqa Begum; Mohsan Nawaz; Abdul Wadood; Amal H. Al-Bagawi; Ahmed M. Aref; Mohamed A. Fareid; Rashid Iqbal (Results in Chemistry)
1,2,3-benzotriazole-based Schiff base derivatives were synthesized, characterized through different techniques such as 1HNMR, 13CNMR, and HREI-MS, and screened against the alpha-glucosidase enzyme. All the synthesized analogues showed good inhibitory potentials with IC50 values ranging from 2.20 ± 0.30 μM to 24.40 ± 0.10 μM as compared to the standard drug acarbose (IC50 = 10.30 ± 0.20 μM). The most potent analogues among the series are 3 (IC50 = 4.30 ± 0.20 μM), 8 (IC50 = 9.40 ± 0.10), 9 (IC50 = 6.20 ± 0.40), 10 (IC50 = 6.60 ± 0.20), 11 (IC50 = 6.10 ± 0.30), 12 (IC50 = 4.70 ± 0.50 μM), 13 (IC50 = 2.20 ± 0.30 μM), 14 (IC50 = 4.30 ± 0.20 μM), and 16 (IC50 = 7.40 ± 0.20), which were found manyfold more active than the standard drug acarbose. A structure-activity relationship study was established that significantly depends on the position, nature, number, and electron-donating/withdrawing effect of the substituent(s) attached to the phenyl ring. We conducted molecular docking studies to investigate the binding interaction of the most potent analogues with the active site of an enzyme.